Pengaruh Metode 5’s (Swaddling, Side/Stomach Position, Sushing, Swinging Dan Sucking) Terhadap Respon Nyeri Pada Bayi Setelah Imunisasi Dasar - Hidayah, Arinil; Habibah, Nursalmah (Universitas Aufa Royhan, 2023)
Immunization that is injected into the baby's body can cause pain or disomport in the baby. The pain experienced by baby when immunization is an emotional experience that makes baby uncomfortable due to tissues damag on the baby's body. The purpose of this research is to find out Effect of the 5'S method (Swaddling, Side/Stomach Position, Sushi, Swinging and Sucking) on ​​reduce pain in infants after basic immunization injections. This research method uses a quasi-experimental, use the One Group Pre-test research design and Post-test without control group. The sample used in this study was total sampling, namely mothers who came for immunization in Juli, namely as many as 33 people. Statistical test using Wilcoxon test, used to see the effect between two variables with a 95% confidence degree. The results of this study the pain response in infants after injection immunization before doing the 5'S method the majority experienced severe pain. There was a decrease in pain in the baby after immunization after done the 5'S method the majority experienced moderate pain. The conclusion of giving the 5'S method is effective in reduce the pain response of infants aged 0-4 months, based on the concept that 4 months after birth, the baby is not fully ready to be outside the womb, baby longs for comfortable sensation like in the womb. Suggestions for Public Health Center it is hoped that the results of this study can be new information to health workers who is on duty at the time of immunization and can inform the mother, that 5'S action is very useful for babies and explains the negative effects of pain and cries that are not treated immediately addresed